NUTRITIONAL QUALITY OF DUCK EGGS FEED WITH MAGGOTS (Hermetia Illucens) - Adinda Siregar,; Dini Julia Sari Siregar, (Journal of Innovation Research and Knowledge, 2024)
This research aims to determine the effect of giving maggot fresh (Hermetia illucens) to duck feed on the nutritional quality (crude protein, gross energy and crude fat) of duck eggs. The design used was a non-factorial Completely Randomized Design (CRD) with 4 treatments and 5 replications. Egg samples are taken from each replication for testing. The feed treatment given to ducks is as follows: (FP0) 100% commercial feed; (FP1) Commercial feed 75% + Fresh maggot 25%; (FP2) Commercial feed 50% + Fresh maggot 50%; (FP3) Commercial feed 25% + Fresh maggot 75%. The results of the study showed that the treatment (addition of maggot fresh to the feed of laying ducks) had a significant effect (P<0.05) on crude protein, gross energy and crude fat in duck eggs. In terms of crude protein parameters, the addition of fresh maggots to duck feed had a lower average crude protein in the eggs produced compared to the 100% commercial feed control treatment. However, for the gross energy content and crude fat contained in duck eggs, the addition of fresh maggots to the duck feed gave higher results compared to the control treatment, namely commercial feed